Teachers' Knowledge and Use of Evidenced-Based Practices for Students With Autism Spectrum Disorder in Saudi Arabia - Alhossein, Abdulkarim (Frontiers in Psychology, 2021)
The evidenced-based practices (EBPs) movement in the field of special education began ~20 years ago. This study contributes to that literature. It investigates the teachers' knowledge and use of EBPs to teach students with autism spectrum disorder (ASD) in Saudi Arabia. The Teachers' Knowledge and Use of EBPs Survey was administered to 240 special education teachers. The participants generally reported a medium level of knowledge and use of EBPs for students with ASD. Female teachers' use of EBPs was greater than that of males, and teachers who attended more than five professional development programs reported greater use of EBPs than those that attended fewer programs. Knowledge and use of EBPs were related. Gender and professional development programs were predictors of teachers' use of EBPs for students with ASD. Teachers' knowledge of EBPs for students with ASD is a vital indicator of teachers' use of those practices, professional development programs can improve such knowledge and use, and teachers' use of EBPs for students with ASD could be improved by offering high-quality professional development programs.